Letter from Hans Smit, Fuld Professor of Law, Director of Parker School and Comparative Law, Columbia University - Smit, Hans (Columbia Journal of Asian Law, 1987)
Letter from Hans Smit, Fuld Professor of Law, Director of Parker School and Comparative Law, Columbia University